Meta Analisis: Pengaruh Lingkungan Keluarga dan Sekolah Terhadap Perilaku Sosial-Emosional Pada Anak Usia Dini - Alfina Fatwa Khasanah; Alfiah Maulia; Wirdah Syifa Fauziah; Fidrayani Fidrayani (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to analyze the influence of family environment interactions on the social-emotional behavior of early childhood. The aim of this research is to find out how much influence family environment interactions have on the social-emotional behavior of early childhood. The method used is meta-analysis, by describing the results of analysis from various studies that have been published nationally in Indonesia, then calculating the effect size. The research sample consisted of ten articles published in accredited national journals in the 2017-2021 period. The instrument used is a coding sheet containing data and information on findings from each article. The results of the analysis show that the average correlation value between family environment interactions and early childhood social-emotional behavior is 0.71, which is included in the high category. These findings indicate that interactions in the family environment have a significant influence on the development of social-emotional behavior in early childhood, and play an important role in forming positive behavior in children.